Pengaruh Penerapan Manajemen Risiko terhadap Kinerja Keuangan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2019–2021 - Jafrina, Meri; Soufyan, Dara Angreka (Medan Resource Center, 2024)
Risk management has become a critical component of banking governance in response to increasing financial complexity and systemic vulnerability. This study examines the influence of credit risk management, liquidity risk management, and operational risk management on the financial performance of banking institutions listed on the Indonesia Stock Exchange during the period 2019–2021. The research addresses the extent to which the implementation of risk management practices contributes to variations in banks’ financial outcomes. Employing a quantitative research design, this study uses purposive sampling to select 16 banking companies and applies multiple linear regression analysis to evaluate the relationships among variables. The empirical findings demonstrate that credit risk management, liquidity risk management, and operational risk management exert a significant influence on banks’ financial performance. These results indicate that effective risk management implementation enhances financial resilience and supports sustainable banking performance. The study concludes that comprehensive risk management practices play a decisive role in shaping the financial performance of banking institutions and should be strengthened as part of strategic financial governance. This research contributes to the literature by providing empirical evidence from the Indonesian banking sector and offers insights for policymakers and banking practitioners in optimizing risk management framework.